2021
DOI: 10.1186/s40001-021-00505-x
|View full text |Cite
|
Sign up to set email alerts
|

ROSE in Rosai–Dorfman–Destombes (RDD) disease: a cytological diagnosis

Abstract: Background Rosai–Dorfman–Destombes (RDD) is also known as sinus histiocytosis with massive lymphadenopathy (SHML). It is a benign proliferative disorder of histiocytes, affecting lymph nodes, rarely with extra-nodal involvement. Rapid on-site evaluation (ROSE) with fine-needle aspiration cytology (FNAC) can be utilized as a minimally invasive investigation to avoid unnecessary surgery of this self-limiting disease. Case presentation A 65-year-old f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…RDD is a well-de ned clinicopathological entity, rst described by Destombes in 1965. [6,21] Later in 1969, Juan Rosai and Ronald Dorfman, recognized it as a distinct disease entity comprising sinus histiocytosis and massive lymphadenopathy [9,21] and previously classi ed by the Working Group of the Histiocyte Society of 1987 as a non-Langerhans cell (LC) histiocytosis. [25] This same society has recently reclassi ed the histiocytoses based on new insights into the pathological, genetic and molecular features of these disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RDD is a well-de ned clinicopathological entity, rst described by Destombes in 1965. [6,21] Later in 1969, Juan Rosai and Ronald Dorfman, recognized it as a distinct disease entity comprising sinus histiocytosis and massive lymphadenopathy [9,21] and previously classi ed by the Working Group of the Histiocyte Society of 1987 as a non-Langerhans cell (LC) histiocytosis. [25] This same society has recently reclassi ed the histiocytoses based on new insights into the pathological, genetic and molecular features of these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…RDD (Rosai Dorfman disease), previously also called Sinus histiocytosis with massive lymphadenopathy, was rst described by Rosai and Dorfman in 1969. [1,9,11] It is a self-limiting histiocytic disease with unknown etiology. Non-tender, painless lymphadenopathy in young patients, usually in the rst or second decades of life, is characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…The differential diagnosis of RDD related to clinical and histological features can include reactive lymph node hyperplasia, infectious lymphadenitis, Langerhans cell histiocytosis, non‐Hodgkin's lymphoma, and metastatic carcinoma. 23 Because of its self‐limiting nature as well as less incident rate, no standard treatment protocol has been made for RDD. A review of the literature revealed that 50% of patients with RDD require no treatment and that 82% of untreated patients experience spontaneous and complete disease regression.…”
Section: Discussionmentioning
confidence: 99%
“…Although any age group can be affected, most of the patients are younger than 20 years [16]. It presents with gradual painless bilateral cervical lymphadenopathy, fever, raised ESR, hypergammaglobulinemia, and occasionally anemia [17].…”
Section: Rosai Dorfman Diseasementioning
confidence: 99%
“…The diagnosis can be confirmed by using IHC markers. Characteristically, S100 is always positive along with other markers, like CD68, CD163, α1 anti-chymotrypsin, and α1 anti-trypsin, negative for CD1a and Langerin (CD207) [17]. The differential diagnoses include reactive lymph node hyperplasia (RLH), infectious lymphadenitis, Langerhans cell histiocytosis (LCH), non-Hodgkin's lymphoma, and metastatic carcinoma [18].…”
Section: Rosai Dorfman Diseasementioning
confidence: 99%